Injuries in sports karate - Tatiana Tapajčiková (Matej Bel University, 2022)
Karate is one of the most popular sport. It belongs to contact martial arts, which causes a number of injuries. Injuries do not occur only during the match; they mostly occur during training, warm-up, or training of techniques or situations. Factors that affect the incidence of injuries are many, whether it is age, gender, experience of the athlete, weight, physical fitness, or mental state of the athlete. The most common areas of the body injured are face and head, lower extremities, the trunk, upper extremities. Awareness of coaches and athletes about injuries in their treatment and prevention will help reduce the incidence of injuries in karate, as well as in other sports.